Pengembangan Game Monopoli Zat Aditif Dan Tekanan Zat Padat Menggunakan Adobe Flash Terhadap Pemahaman Konsep Ipa Kelas VIII - nurhasnah, nurhasnah; fildzah, Hijatul (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
Research has been conducted on monopoly game learning media using Adobe Flash using the research and development (R & D) research method using the Plomp model. The sample used for testing monopoly game learning media using Adobe Flash was 21 students of VIII B class of Saniangbaka. The testing instrument was validated by the lecturer at Tadris IPA Concentration in Physics UIN Imam Bonjol Padang. The test results show a good response to the understanding of studentsâ€™ concept through practicality result of 86 % and the result of of the effectiviness of learning media monopoly game using Adobe Flash obtained 86,19 %. Result this indicates that learning media in the form of monopoly games using Adobe Flash are suitable for use as learning media.Â